Computational method and program for generating a porous scaffold based on implicit surfaces. (June 2021) - Iamsamang, Jirawat; Naiyanetr, Phornphop
Highlights: This proposed program and method generate the 3D mesh of porous structure from the user-input 3D model. The program can observe the pore size, porosity, and surface area ratio of the generated 3D mesh. The optimal pore size and porosity can be archived by adjusting the program parameters. Abstract: Background and objective: The triply periodic minimal surface (TPMS) method effectively mimics the porous scaffold for tissue engineering with continuous topology, pore interconnections, and high surface area to volume ratio. However, the process to generate a three-dimensional (3D) mesh of porous structure from the mimicked organs is complicated for biologists and sometimes requires various software. Herein, we present the standalone program called "Scaffolder" for generating the porous topology from the user-input 3D model to the open-source community. Methods: The 3D mesh of a porous scaffold was used by the proposed method and dual-marching cubes algorithm. Afterward, the mesh was sliced into the contours to examine pore sizes by Feret diameter and Gilbert–Johnson–Keerthi distance. The relationships between the program parameters (i.e., grid size, angular frequency, and iso-level) and scaffold properties (i.e., pore size, porosity, and surface area ratio) were investigated. Results: The developed program can generate and evaluate a porous scaffold. The median (IQR) absolute errors in grid size of 200, 300, 400, and 500 divisions were 1.92 (0.35-3.80), 1.00 (0.18-2.22), 0.53 (0-1.37), and 0.24 (0-0.74), respectively. Spearman's correlation showed the impact of angular frequency and iso-level on the pore size, porosity, and surface area of the generated scaffold (p<0.05). Conclusions: This study enables researchers to rapidly design the 3D mesh of porous scaffold design, evaluate scaffold properties, and customize the implicit function for various applications, especially in tissue engineering and computational structural analysis. Graphical abstract: The figure shows the overall scaffold generation procedure from the user-input 3D model, parameters, and TPMS function to the final porous scaffold mesh. Image, graphical abstract